Knowledge and attitudes towards COVID-19 among emergency medical service workers - Vatan,Asli (2020)
SUMMARY OBJECTIVE: Good knowledge of the coronavirus disease 2019 (COVID-19) among healthcare workers is essential for keeping health systems active and controlling the outbreak. We aimed to investigate the knowledge and attitudes of Emergency Medical Service (EMS) employees who fight COVID-19 at the forefront. METHODS: A total of 400 EMS workers (doctors, nurses, emergency medical technicians, paramedics, and ambulance drivers) were included in this study. Knowledge, attitude, and preventive behaviors for COVID-19 were evaluated using an online questionnaire. RESULTS: A total of 275 EMS workers participated in the study with a response rate of 68.8%. The respondents reported that their highest common sources of knowledge about COVID-19 were social media and television (n=240, 88%). Overall, > 96% of the participants had adequate knowledge about the transmission routes of COVID-19. Among the respondents, 36% of them were unaware of the correct hand washing or scrubbing technique. In addition, 78% of the participants had poor knowledge about floor and surface disinfection. The majority of the participants exhibited inaccurate attitudes toward the use of personal preventive equipment. More than half of EMS workers (52%) agreed that a surgical mask is not enough during the procedures that do not generate aerosol. Moreover, a significant proportion of the participants (66%) perceived that a N95 mask is required. CONCLUSIONS: As a consequence, although emergency workers have sufficient basic knowledge about COVID-19, there is a need for postgraduate training in many subjects.